ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS BERDASARKAN GENDER SISWA KELAS X SMA NEGERI 1 KAWANGKOAN BARAT DALAM MENYELESAIKAN SOAL BARISAN DAN DERET ARITMATIKA - Pantow, Tesalonika Angely; Mangobi, James U. L.; Ermita, Ermita (SOSCIED, 2025)
Mathematics trains one to think systematically, scientifically, critically, and creatively. Creative thinking such as Critical Thinking Skills, Creative Thinking Skills, Communication Skills, and Collaboration Skills are competencies needed in the second century. This research will be conducted in SMA Negeri 1 Kawangkoan Barat, Minahasa Regency, North Sulawesi Province. The subject selection technique in this study used a data source subject selection technique with certain considerations. Data were collected with questions that refer to 4 indicators and after the data were collected, descriptive quantitative analysis was conducted. The results obtained showed that the mathematical creative thinking ability of students at the SMA Negeri 1 Kwangkoan Barat level as a whole was in the moderately creative category with the results of indicators from highest to lowest, namely fluency 36%, flexibility 26%, originality 20%, elaboration 18%.